β-Arrestin1 and Signal-transducing Adaptor Molecule 1 (STAM1) Cooperate to Promote Focal Adhesion Kinase Autophosphorylation and Chemotaxis via the Chemokine Receptor CXCR4 - Alekhina, Olga (J Biol Chem, 2016)
The chemokine receptor CXCR4 and its chemokine ligand CXCL12 mediate directed cell migration during organogenesis, immune responses, and metastatic disease. However, the mechanisms governing CXCL12/CXCR4-dependent chemotaxis remain poorly understood. Here, we show that the β-arrestin1·signal-transducing adaptor molecule 1 (STAM1) complex, initially identified to govern lysosomal trafficking of CXCR4, also mediates CXCR4-dependent chemotaxis. Expression of minigene fragments from β-arrestin1 or STAM1, known to disrupt the β-arrestin1·STAM1 complex, and RNAi against β-arrestin1 or STAM1, attenuates CXCL12-induced chemotaxis. The β-arrestin1·STAM1 complex is necessary for promoting autophosphorylation of focal adhesion kinase (FAK). FAK is necessary for CXCL12-induced chemotaxis and associates with and localizes with β-arrestin1 and STAM1 in a CXCL12-dependent manner. Our data reveal previously unknown roles in CXCR4-dependent chemotaxis for β-arrestin1 and STAM1, which we propose act in concert to regulate FAK signaling. The β-arrestin1·STAM1 complex is a promising target for blocking CXCR4-promoted FAK autophosphorylation and chemotaxis.